The Impact of Stationery Rewards on the Reading Frequency of Grade 4 Students: An Experimental Study - Nuriana, Zulfa Ilma; Azzahro, Asri Fattia; Hanggara, Bayu Sukma; Aminah, Ummi (Yayasan Sinergi Kawula Muda, 2024)
This study investigates whether providing stationery rewards can increase the reading frequency of 4th-grade students at an elementary school in Wonorejo Village, Blitar Regency, East Java. The research adopts an experimental within-subject design, utilizing primary and secondary data sources. Primary data were collected through direct observations and structured interviews, while secondary data were obtained from relevant literature. The research applied a quantitative approach with a repeated-measures technique for analysis. Validity was ensured through controlled experimental conditions, and reliability was achieved through repeated trials over ten days. The results indicate that while the provision of rewards led to a temporary increase in reading frequency, the effect was not sustained once the intervention ceased. The discussion highlights the limitations of extrinsic motivation in sustaining long-term behavioral changes and suggests alternative strategies for improving reading habits. The study concludes that while rewards can serve as an initial motivator, a comprehensive approach integrating intrinsic motivation is necessary for lasting improvements. This research is significant as it provides insights into effective literacy development strategies in elementary education.